The Ronsu Scale: Unveiling a Robust Tool for Assessing Recovery-Oriented Nursing Services Utilization among People with Schizophrenia - Thongsalab, Jutharat; Yunibhand, Jintana; Juanamasta, I Gede (Fakultas Ilmu-ilmu Kesehatan, 2025)
Recovery-oriented nursing services (RONS) have emerged as a significant paradigm in the treatment of schizophrenia. Nevertheless, the number of validated instruments available to assess patient utilization of these services is insufficient. This study aimed to develop and validate the Recovery-Oriented Nursing Services Utilization (RONSU) scale. A cross-sectional study was conducted to develop the scale for adults aged 18 and older who older residing in the community who have schizophrenia, between March and May 2023. Participants from six hospitals had participated in outpatient mental health nursing for at least eighteen months following discharge. The scale development followed the seven-step process outlined by DeVellis and Thorpe. An exploratory factor analysis conducted on 110 samples identified a four-factor structure, comprising the following components: social skill training, indirect nursing care management, therapeutic nurse‒patient relationships, and coping skill training. With the assistance of 231 participants and confirmatory factor analysis, the RONSU was refined to 32 items across the four dimensions. The construct's validity and reliability were confirmed, as the fit indices and composite reliability fell within acceptable bounds. The RONSU scale contributes in both scholarly and clinical spheres, enhancing the understanding and application of recovery-oriented nursing services for individuals with schizophrenia